Cooking the Vietnamese way : revised and expanded to include new low-fat and vegetarian recipes / Chi Nguyen; Judy Monroe Peterson - Nguyen, Chi
An introduction to the cooking of Vietnam featuring such recipes as spring rolls, sweet and sour soup, and Vietnamese fried rice. Also includes information about the land, history, and holidays of this south-east Asian country.